'A Token of Gratitude'? A Morally Ambiguous Case of Bribery - Jacobsson, Katarina (Journal of Scandinavian studies in criminology and crime prevention, 2006)
The phenomenon of bribery is characterized by its elastic features, both morally and legally. This study sets out to investigate a court case of bribery: how the people involved construct and argue for their particular version. A single case of bribery is chosen in order to clarify the range and potential of various descriptions of the very same event. The material consists of interviews with the parties involved: a male lawyer who was charged with bribery, a female court clerk for whom the bribe/gift was intended, and the prosecutor who handled this specific case. When telling their stories-representing a non-criminal and an illegitimate version of the event-they also construct two perspectives as incompatible: 'the right [legal] way' and 'the human way'. With regard to these perspectives it is not only the convicted lawyer who accounts for his actions, but also the clerk and the prosecutor